The influence of season, locality, ascending steeping and germination times on the malting quality of four barley cultivars - Terblanche, Stephanus Esaias (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1965.